The Prospect Of Heat Shock Protein (Hsp) As Biomarker Of Oral Disease - Nurul Amin, Muhammad (Insisiva Dental Journal, 2012)
The prevalence of oral diseases is increasing and caused by many factors. It can be caused by environmental, genetic, malignancy or side effects of dental treatment. The research detect these disease has been done, but still not getting satisfactory results. Heat shock proteins (HSP) are intracellular proteins that mediate the cytoprotective function and other essential functions. This protein is expressed and synthesized under conditions of stress/harmful or nonstress. The oral disease is a form of adverse conditions, and the course will also trigger HSP expression.